KEWAJIBAN MORAL DAN KEWAJIBAN HUKUM: KAJIAN FILSAFAT HUKUM DENGAN RELEVANSI BAGI DISKURSUS HUKUM INDONESIA - Wawan Haryanto (Program Studi Hukum Tata Negara (Siyasah) IAIN Palopo, 2025)
This article examines the conceptual relationship between moral obligation and legal obligation through a normative philosophy of law approach. By analyzing the theories of Hans Kelsen, H. L. A. Hart, Lon Fuller, and John Finnis, the study formulates a conceptual framework for understanding how moral norms and legal norms are interconnected, how they differ, and how they may reinforce one another. Special attention is given to the relevance of this discourse within the Indonesian legal context, particularly in understanding: (1) conflicts between conscience and the duty to obey the law; (2) the foundations of legal legitimacy beyond mere procedural formality; (3) the role of morality in the processes of lawmaking and legal interpretation; and (4) normative critiques of laws deemed unjust. The article concludes that although moral obligations and legal obligations can be conceptually distinguished, a stable and legitimate legal system requires a meaningful integration of moral dimensions as its normative foundation—especially in a pluralistic society such as Indonesia, which recognizes Pancasila as the foundational legal principle embodying moral values.